Biomolecular Characteristics of Amyloid Precursor Protein Mutations As Causes of Alzheimer's Disease Analyzed Through Bioinformatics Media: Biomolecular Characteristics of Amyloid Precursor Protein Mutations As Causes of Alzheimer's Disease Analyzed Through Bioinformatics Media - Irfannudin, Irfannudin (Sriwijaya Journal of Medicine, 2018)
Methods of biomolecular analysis on protein through bioinformatics media has been growing rapidly. This report is intended to describe the results of biomolecular amyloid precursor protein (APP) analysis and the characteristic change of APP mutations causing cognitive degeneration disorder through bioinformatics media and search to reliable biomolecular sites. APP is a transmembrane protein that is widely present in neuronal tissue. APP plays an important role for the formation of neuronal cells. The APP gene is located on the 21st chromosome that has 290,586 base pairs (bp) of 20 exons and 19 introns. In the form of a protein, APP consists of 770 amino acids with major expressions located on the cell surface. Mutation of APP genes is believed to play a role in the incidence of Alzheimer's disease. One of the mutations studied in this paper is the mutation of Alanin to Glysin at the position of the 692 amino acid (APP mutant A692G). This mutation affects the impairment of cerebral amyloid angiopathy belonging to the Alzheimer Disease Familial-1 group.These mutations do not cause changes in predictions of secondary structures and only cause slight changes in molecular weight, amino acid composition, atomic composition, aliphatic index, hydroplasticity and stability index. APP A692G mutation does not alter topology, hydrophobicity, cutting prediction and protein location prediction. Mutation also removes only the side chains at the position of the mutated amino acids.